Themed editorial: How can the emergence of digital nomadism be operationalized in tourism development? - Ozgit, Hale; Ozturen, Ali; Gunay, Semra; Ilhan, Oznur Akgis (Emerald Group Publishing Ltd, 2024)
[Abstract Not Available]